Human Resource Management Practices and their Impact on the Performance of the Personnel of the Ministry of Regional Municipalities and Water Resources in the Sultanate of Oman - Al-Abri, Laila; Al-Hadrami, Ahmed (The Arab Journal of Administration, 2022)
The study attempted to identify the level and impact of human resource management practices on the performance of workers in the Ministry of Regional Municipalities and Water Resources in the Sultanate of Oman, by clarifying the importance of the contribution of human resources management practices in achieving excellence in the performance of workers in the Ministry of Regional Municipalities and Water Resources in the Sultanate of Oman. The researchers relied on the descriptive analytical approach, and by selecting a sample of workers in the Ministry of Regional Municipalities and Water Resources consisting of (32 workers). A questionnaire was applied to them, using the tools of arithmetic means and standard deviations of the SPSS statistical program. The researchers found a high level of human resource management practices among workers in the Ministry of Municipalities Regional and Water Resources in the Sultanate of Oman. The results showed that the general level of the sample reached an arithmetic average of 3.83, which is a high level, and the level of responses of the sample members to the thirty paragraphs of the questionnaire ranged between 3.14 and 4.23, which are average rates between high and very high, which indicates the high level of human resource management practices in the study sample.